Water Quality Assessment and Characterization of Bacteria Species from Jangoi River and Sikog Waterfall, Padawan, Sarawak - Stanley Sait, Agusti (Malaysian Journal of Microbiology, 2023)
Natural recreational waters, including rivers and waterfalls, are popular among locals and visitors in Sarawak. However, the water quality of Sarawak’s natural recreational waters has not been the subject of much research. Jangoi River and Sikog Waterfall were chosen as research sites as both are popular spots for recreational purposes. Due to human activities, the water quality status needs to be monitored and bacterial diversity also needs to be identified as users could be exposed to potentially pathogenic bacteria. This research focuses on water physicochemical quality assessment and bacteriological analysis of recreational streams, which helped determine the water quality status, and factors contributing to contamination of rivers such as land-use practices and their impact on the water body. Thus, Water Quality Index (WQI) was utilized and determined based on the dry and wet seasons, and the water quality was classified according to National Water Quality Standard (NWQS) for the Malaysian River. In addition, it is crucial to study the dissemination of the bacterial communities in the research area along with their antibiotic resistance profiles based on commonly used antibiotics in clinical and agricultural settings in order to have a data baseline that could be useful for the use of health care providers and the public. This study aims to assess the quality of the recreational river water, isolate and characterize diverse types of bacterial species from recreational water and determine the antibiotic susceptibility of bacteria isolates towards different antibiotics. The in-situ and ex-situ water quality analysis of Jangoi River and Sikog Waterfall were performed following APHA (2005) methods, and the genetic profiles of bacterial isolates were determined using (GTG)5 PCR genetic fingerprinting and Gel J software. Furthermore, the antibiotic susceptibility of bacteria isolates was determined using Kirby-Bauer disk diffusion method to determine their level of susceptibility and to ensure the continued effectiveness of antibiotics. Overall, the iv Water Quality Index results show that Jangoi River and Sikog Waterfall have excellent water quality values ranging from 89-98. The isolates were grouped into a dendrogram based on their genetic similarities index, ranging from 73% to 80% similarities, and only 73 of the 180 bacteria isolated from Jangoi River and Sikog Waterfall were selected for further identification using 16S rRNA PCR and sequencing analysis. The 73 isolates constitute of 20 bacteria genera, including Enterobacter (16%), Pseudomonas (11%), Rossellomorea (10%), Kosakonia (7%), Aeromonas (7%), Chromobacterium (5%), Escherichia (5%), Stenotrophomonas (5%), Staphylococcus (5%), Bacillus (5%), Alcaligenes (3%), Citrobacter (3%), Klebsiella (3%), Serratia (3%), Cronobacter (3%), Pantoea (3%), Kocuria (1%), Lysinibacillus (1%), Paenalcaligenes (1%), and Plesiomonas (1%). Based on AST result, the highest rate of resistance was shown against streptomycin (10 μg) (33.33%) and ampicillin (10 μg) (33.33%), followed by penicillin (10 units) (25.00%), and erythromycin (15 μg) (18.75%). Lysinibacillus tropicus has the highest MAR index of 0.50, followed by Bacillus cereus (0.18) and Paenalcaligenes faecalis (0.15). In conclusion, the data from the bacteriological aspect provide additional and relevant information regarding the distribution of bacterial species in recreational water and their antibiotic susceptibility profiles, which may be beneficial for clinical reference when treating bacterial infections.